"They are teaching us to deliver lessons and that is not all that teaching is …": Exploring teacher trainees' language for peer victimisation in schools. (March 2020) - Fry, Deborah; Mackay, Kirsteen; Childers-Buschle, Kristin; Wazny, Kerri; Bahou, Lena
Abstract: This paper reports on qualitative findings from the larger Safe Schools Longitudinal Study and explores what trainee teachers understand by the term 'bullying', its prevalence, and the barriers to responding to it. Twenty-four teacher trainees at an Initial Teacher Education programme in Scotland took part in two waves of qualitative interviews three years apart. Findings show trainee teachers use the term 'bullying' to cover a range of behaviours - with uncertainty around whether verbal insults are bullying. Key factors that impact teacher responses are discussed - with the attitude of the head teacher being pivotal to school climate. Highlights: Trainee teachers have a limited vocabulary for describing peer victimisation. Verbal insults are less likely to be defined as 'bullying' by trainee teachers. Trainee teachers feel university training inadequately prepares them for addressing peer victimisation. Trainee teachers undertaking placements in schools emphasising anti-bullying felt more supported and confident.